Life and times of Cantoo Baboo (Krisna Kanta Nandy), the banian of Warren Hastings : period covered, 1742-1804 - Nandī, Somendracandra (Allied, 1978)
On the life and work of the Bengali silk and salt merchant Krisna Kanta Nandy, 1720-1794, and founder of the Cossimbazar royal family of Murshidabad District, West Bengal.